Richard's Self-Actualization In Richard Wright's Black Boy:A Humanistic Psychological Approach - Romdiyati, Romdiyati (2003)
The object of the research is a fictional authobiographical novel BLACK BOY (1945) by Richard Wright. The study is focused on self-actualization of the major character from humanistic psychological perspective. The aim of the study is to show the effort of Richard to reach his self-actualization. In conducting the study, the writer uses qualitative method. The primary source is the novel itself, and the secondary sources are the author biography, the humanistic theory, theories of literature, and other books that relevant to this research. Method of collection data is documentation and library research, while the data analyzing technique is descriptive and hermeneutics. The writer uses Humanistic theory as a technique of analysis. The result of the study shows that human will be motivated to attain his self-actualization after gratifying the lower needs (basic needs). A person will develop himself, to be what he wants to be and to reach the goal in life. He will try to grow greater and uses his potential into the fullest.